Assessment of hydrological connectivity characteristics of riparian zones and their correlation with root–soil composites at different bank heights of a first-class river in China - Yang, Qihong; Zhang, Chaobo; Liu, Xiaoguang; Yao, Shiming; Huang, Renyong (Frontiers in Ecology and Evolution, 2023)
The unreasonable utilization of riparian zones is an important ecological and environmental problem, which seriously threatens the sustainable development of the environment. Under the combined effects of topography and vegetation, it is a new idea to analyze the hydrological connectivity of riverbank slopes based on dye-tracer technology. To quantify the hydrological connectivity in root-soil composites, dyeing and tracing experiments were carried out on the plots at different heights on the banks of the Fen River. The results showed that the soil dyeing area ratio was different in the different soil profiles and soil depths. The dyeing area ratio, maximum dyed depth, length index, peak value and non-uniformity coefficient of the high plot were all greater than those of the low plot. The index of hydrological connectivity was found to be greater for Pc2 (High plot) than Pc1 (low plot) in the study area. There was no significant correlation between the index of hydrological connectivity and the physical properties of the soil at different depths, and the soil hydrological connectivity was closely related to the plant roots with diameter less than 1mm. The results of this study provide more information for the assessment of the hydrological connectivity of root-soil composites.